PROSEDUR PEMERIKSAAN RADIOGRAFI ABDOMEN PROYEKSI LLD PADA KASUS ILEUS OBSTRUKTIF DI INSTALASI RADIOLOGI IGD RSUD ARIFIN ACHMAD PROVINSI RIAU - Ummu Habiba; Abdul Zaky; Annisa (Medical Imaging and Radiation Protection Research Journal, 2021)
On abdominal examination, obstructive ileus was performed in 3 positions, namely Antero Posterior (AP), half sitting and Left lateral decubitus (LLD). LLD projection aims to show free air in the intraperitoneal cavity in cases of acute abdomen, so that the patient remains on the examination table in the left lateral position for 10 to 20 minutes before abdominal radiography is performed. While the abdominal examination of the LLD projection at the ER Radiology Installation at the Arifin Achmad Hospital, Riau Province, did not use the exposure waiting time, so there was a difference between theory and the field. The purpose of this study was to determine the procedure for radiographic examination of the LLD projection of the abdomen in cases of obstructive ileus at the ER Radiology Installation at Arifin Achmad Hospital, Riau Province, by not using the exposure waiting time, to establish a diagnosis. This research is a descriptive qualitative research with a case study approach through library research, field observations, in-depth interviews, and documentation. The research was conducted at the Radiology Installation of Arifin Achmad Hospital, Riau Province from May-June 2020. The procedure for radiographic examination of the LLD projection of the abdomen in the case of obstructive ileus at the ER Radiology Installation at the Arifin Achmad Hospital, Riau Province by not using the exposure waiting time, was able to establish the diagnosis but the resulting radiographic results, namely air fluid levels were not maximal